The Variations of Qur’anic Readings and Their Impact on Semantic and Interpretative Meanings among Exegetes and Grammarians (Journal of human and social sciences, 2024)
The research focuses on studying the multiplicity of meanings for a single word due to differences in letters or diacritical marks within the same word, as seen through the various Quranic readings, their interpretation, and the extent of their syntactic and semantic usage. The differences in Quranic readings have a significant and profound impact on enriching the language, grammar, morphology, semantics, and lexicography. The Quranic readings—both the widely accepted and rare ones—are rich in linguistic material. It may be beneficial for the enrichment of the language to gather the scattered rare readings from books of exegesis, jurisprudence, grammar, and lexicons and compile them into a dictionary for the benefit of students of knowledge. The readings are not exclusive to books of Quranic readings alone, but books of exegesis, jurisprudence, lexicons, and grammar are filled with explanations, analyses, and commentary on various readings, from which our scholars have deduced legal, linguistic, and other rulings. The multiplicity and variation of readings fall under the category of diversity, and all are valid, being part of the Quranic miracle. The verses relevant to this research have been compiled to the best of my ability and studied syntactically and semantically. Praise be to God for His guidance and facilitation.
Keywords: Quranic Readings; Grammatical Analysis; Semantics; Inimitability; Arabic Language